2012
DOI: 10.1016/s0140-6736(12)60865-4
|View full text |Cite
|
Sign up to set email alerts
|

Sport and exercise as contributors to the health of nations

Abstract: A. (2012). Sport and exercise as contributors to the health of nations. The Lancet, 380, 59-64.Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.sciencedirect.com: http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
281
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(318 citation statements)
references
References 41 publications
5
281
1
12
Order By: Relevance
“…Since classic papers of Jerry Morris and colleagues indicating association between occupational physical activity (PA) and risk of coronary heart disease, numerous subsequent epidemiological studies have confirmed that regular exercise may prevent from chronic non-communicable diseases, improve well-being and considerably contribute to an increase in life expectancy [1][2][3][4][5][6]. More importantly, there is an increasing body of evidence that not only leisure-time, but also commuting activity connected with travelling to work or school may substantially modify the risk of cardiovascular and metabolic disorders [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Since classic papers of Jerry Morris and colleagues indicating association between occupational physical activity (PA) and risk of coronary heart disease, numerous subsequent epidemiological studies have confirmed that regular exercise may prevent from chronic non-communicable diseases, improve well-being and considerably contribute to an increase in life expectancy [1][2][3][4][5][6]. More importantly, there is an increasing body of evidence that not only leisure-time, but also commuting activity connected with travelling to work or school may substantially modify the risk of cardiovascular and metabolic disorders [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The balance between health benefits the potential injury associated with sport firmly swings towards health benefits (Khan et al, 2012). However, in the case of elite athlete, injury has far greater meaning with respect to career and financial stability for the individual or team.…”
Section: Exercise Demands Medicinementioning
confidence: 99%
“…The IOC has already demonstrated its leadership capability in the establishment of programs such as Sport for All [95], Olympic Day Celebrations [96,97], IOC Medical Commission initiatives such as health and fitness for young people through physical activity and sports [98] and education programs [99][100][101], the Youth Olympic Games [102], and through its collaboration with the WHO [6] and the UN [7]. The Olympic Games and the Olympic brand itself are based on positive universal values, which give it a powerful, emotive and unique identity that transcends sport and resonates strongly with people of all ages and cultures from around the world [103].…”
Section: Growing and Scaling Prevention Programs And Centresmentioning
confidence: 99%